BMPR1A and BMPR1B Missense Mutations Cause Primary Ovarian Insufficiency (2020)
CONTEXT: Primary ovarian insufficiency (POI) is a frequently occurring disorder affecting approximately 1% of women under 40 years of age. POI, which is characterized by the premature depletion of ovarian follicles and elevated plasma levels of follicle-stimulating hormone, leads to infertility. Although various etiological factors have been described, including chromosomal abnormalities and gene mutations, most cases remain idiopathic. OBJECTIVE: To identify and to functionally validate new sequence variants in 2 genes that play a key role in mammalian ovarian function, BMPR1A and BMPR1B (encoding for bone morphogenic protein receptor), leading to POI. METHODS: The impact on bone morphogenic protein (BMP) signaling of BMPR1A and BMPR1B variants, previously identified by whole-exome sequencing on 69 women affected by isolated POI, was established by different in vitro functional experiments. RESULTS: We demonstrate that the BMPR1A-p.Arg442His and BMPR1B-p.Phe272Leu variants are correctly expressed and located but lead to an impairment of downstream BMP signaling. CONCLUSION: In accordance with infertility observed in mice lacking Bmpr1a in the ovaries and in Bmpr1b-/- mice, our results unveil, for the first time, a link between BMPR1A and BMPR1B variants and the origin of POI. We show that BMP signaling impairment through specific BMPR1A and BMPR1B variants is a novel pathophysiological mechanism involved in human POI. We consider that BMPR1A and BMPR1B variants constitute genetic biomarkers of the origin of POI and have clinical utility. © Endocrine Society 2019. All rights reserved. For permissions, please e-mail: journals.permissions@oup.com.